The Influence of Organizational Culture and HR Competency on Employee Commitment and Their Impact on Organizational Performance - Vivi Nila Sari; Hamdy Hady; Elfiswandi Elfiswandi (Universitas Pendidikan Ganesha, 2023)
There are several factors that affect Organizational Performance through Employee Commitment including Organizational Culture and HR Competencies. This study aims to empirically test and prove the direct influence of Organizational Culture and HR Competencies on Employee Commitment. The direct influence of Organizational Culture and HR Competencies on Organizational Performance and the influence of Organizational Culture and HR Competencies indirectly through the mediation of Employee Commitment to Organizational Performance. This study used a quantitative approach. The population consists of the State Civil Apparatus (ASN) of the West Sumatra Tourism Office. This study is a population census study with a sample of 248 people. Partial Least Square (PLS) analysis method with SmartPLS Application. The results showed that the accepted hypothesis that Organizational Culture and HR Competencies have a direct impact on employee commitment and the influence of the construct of Organizational Culture and HR Competencies on organizational performance whose hypothesis is accepted. The employee commitment variable in this study cannot be a mediator variable of Organizational Culture and HR Competence variables. The results of this research are expected to advance the science of human resource management and behavior for the benefit of both academics and practitioners.